Pemilihan Guru Berprestasi Taman Kanak-Kanak (TK) dengan Simple Additive Weighting (SAW) - Hamidah Hamidah; Okkita Rizan; Hengki Hengki (Fakultas Ilmu Komputer, Universitas Klabat, 2022)
Based on Law Number 20 of 2003 concerning the National Education System, Article 1 point 14 states that early childhood education is a coaching effort aimed at children from birth to the age of six which is carried out through the provision of educational stimuli to help growth and physical and mental development. spiritually so that children have readiness to enter further education. To support this understanding, quality human resources are urgently needed as a priority for national development, the position and role of teachers is increasingly important in preparing the nation's young generation, especially in facing the current global era. The problem that occurs in the selection of outstanding teachers in early childhood education is that the selection is still subjective, causing it to be unfair. For this reason, a decision support system is needed that can overcome these problems by using the Simple Additive Weighting (SAW) method as a basis for decision making. The method uses 5 criteria, namely education, pedagogy, professionalism, personality and social. The purpose of the support system is to make it easier and faster to determine outstanding teachers so that decisions are objective. Based on the results of the calculations in this study, the results for teacher 1 with a value of 0.85, teacher 2 obtained a value of 0.70, teacher 3 obtained a value of 0.9375, teacher 4 with a value of 0.8625 and teacher 5 with a value of 0.8625 0 ,7625. For this reason, the selection of kindergarten level teachers obtained the best alternative with the highest score being teacher 3 (V3) with a value of 0.9375.